Numerical Simulation on the Evolution of Mining-Induced Fracture Network in a Coal Seam and Its Overburden under the Top Coal Caving Method - Guangdi Deng; Heping Xie; Mingzhong Gao; Cong Li; Zhiqiang He (Advances in Civil Engineering)
The evolution of the fracture network induced by mining has an important influence on the mechanical behavior of the rock and the safety of the mine. In this study, a new 3D modeling approach based on discrete fracture network (DFN) and fractal theory was developed and applied to the Tashan coal mine. The model results of the evolution of fracture in the coal seam are consistent with field observations. The evolution law of fracture network in the overburden strata was studied, and the results show that the fractal dimension of the fractures in the lower strata increased linearly and stabilized quickly within 50 m behind the mining face. In the higher strata, most of the fractures were generated behind the mining face and continued to develop farther than 100 m. More fractures were generated in the lower strata than in the higher strata, and the fractures more easily developed and expanded in the soft rock than in the hard rock. The evolution of the fractures of the main thick hard roof in the lower strata had a great impact on the generation of fractures in the higher strata.